313 Anemia After Aneurysmal Subarachnoid Hemorrhage Is Associated With Poor Outcome and Death. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - MD, Oliver G.S. Ayling; Ibrahim, George; Alotaibi, Naif M; Gooderham, Peter A; Macdonald, R. Loch
Abstract: INTRODUCTION: Anemia after aneurysmal subarachnoid hemorrhage is common and potentially modifiable. Here, we first evaluate the effect of anemia on neurological outcome and death and second, study the effects of packed red blood cell transfusion on outcome. METHODS: A secondary analysis on 413 subjects in the CONSCIOUS-1 study. Multivariable logistic regression identified independent risk factors for anemia and determined the effect of anemia on neurological outcome and death, while adjusting for selected covariates. Optimal predictive thresholds for hemoglobin levels were determined using receiver operator characteristics curve analysis. Finally, patients were pseudorandomized to transfusion using propensity score matching in order to study the effect of transfusions on outcome. RESULTS: Anemia, defined as hemoglobin <10 g/dL, was present in 5% of patients at presentation, in 29% of patients after aneurysm securing (days 1-3), and in 32% of patients during the peak delayed cerebral ischemia (DCI) risk period (days 5-9). Anemia following aneurysm-securing (odds ratio [OR] 1.96, 95% confidence interval [CI] 1.07-3.59, P = .03) and during the DCI window (OR 2.63, 95% CI 1.46-4.76, P = .0014) were independently associated with poor neurological outcome. Anemia postaneurysm securing (OR 3.50, 95% CI 1.15-10.62, P = .027) but not during the DCI window was associated with death. Using propensity score matched cohorts, we found that transfusion of anemic patients did not improve long-term outcome ( P = .8) or mortality rates ( P = .9). Transfusion of patients with a hemoglobin concentration >10 g/dL was associated with improved neurological outcomes ( P = .015, OR 0.09, 95% CI 0.002-0.72), with no differences in mortality. CONCLUSION: Anemia after aneurysmal subarachnoid hemorrhage is associated with poor long-term neurological outcome and death. Transfusion of packed red blood cells is beneficial for patients who are not considerably anemic beforehand, suggesting further work needs to define the threshold but also the time period of anemia that is sufficient and necessary to contribute to poor outcomes.